Production and valuation of foods for animal monogástricos, with biological silage of remains of the prawn prosecution (Litopenaeus vannamei) fermented with lactobacillus - Sánchez, Héctor (2016)
This study allowed the valuation of diets using biological silage of residuals of the prosecution of (Litopenaeus vannamei) EB, fermented inoculum of commercial organisms (Lactobacillos acidofilos) or isolated from the digestive tract of the pig (Enterococcus hirae, Lactobacillus brevis, Lactobacillus johnsonii, Pediococcus pentosaceus) single use in piglets; EB preparation, cooking residues, milling, mixing (molasses and inoculum) and incubation; diet formulation according sp. and physiological state, incorporating EB T0: 0%, T1: 10%, T2: 15% and T3: 20% (in turkeys was used EB 0% 5% 8% 12%), experimenting with 48 (Meleagris gallopavo) fattening stage, 84 (Gallus gallus domesticus) growth and fattening stage, 16 (Sus scrofa domesticus) growth and fattening stage, 8 stage pregnancy-lactation and 64 piglets; We evaluated the feed conversion index (ICA) and digestibility of the diet with EB. Regarding the ICA, the best are: fattening Turkeys T3:2.50; Chicken growth T1:2.35; Pig growth T2:2.89; Chicken fattening T2:2.99; Piglets T2:1.39; pig fattening T3:4.02; gestation sow T1:2.15 and lactating sow T1:3.03. The less efficient are the T0 witnesses. There is statistical similarities between T2, T1 and T3. The food was better digestibility in chickens T2: 84.05 %, pigs T1: 85.71 % and piglets T1: 73.42 %. There is no significant difference between weight increments EB treatments used but differences with T0 treatment (0 % EB). Negative values of weight gain and the ICA in lactation Sows were presented. No digestive problems occurred.